Immune Response in Ovarian Cancer: How Is the Immune System Involved in Prognosis and Therapy: Potential for Treatment Utilization - Nikos G. Gavalas; Alexandra Karadimou; Meletios A. Dimopoulos; Aristotelis Bamias (Clinical and Developmental Immunology)
Ovarian cancer is one of the leading causes of cancer-related death among women. Resistance to the disease occurs in more than 70% of the cases even after treated with chemotherapy agents such as paclitaxel- and platinum-based agents. The immune system is increasingly becoming a target for intense research in order to study the host's immune response against ovarian cancer. T cell populations, including NK T cells and Tregs, and cytokines have been associated with disease outcome, indicating their increasing clinical significance, having been associated with prognosis and as markers of disease progress, respectively. Harnessing the immune system capacity in order to induce antitumor response remains a major challenge. This paper examines the recent developments in our understanding of the mechanisms of development of the immune response in ovarian cancer as well as its prognostic significance and the existing experience in clinical studies.